PERBANDINGAN TINGKAT KESEJAHTERAAN PETANI KENTANG DILIHAT DARI SALURAN PEMASARAN YANG BERASAL DARI DESA MAKAARUYEN KECAMATAN MODOINDING - Rilia R. Dongi; Joachim N.K. Dumais; Esry O.H. Laoh; Lorraine W. Th. Sondakh (COCOS, 2014)
ABSTRAKRiliaRibkaDongi . Comparison of Potato Farmers Welfare Level Seen FromMarketing Channels Originating in the Makaaruyen Village Modoinding Sub District.Under Guidance Ir . Joachim N. K. Dumais , ME as chairman , Dr . Ir .Esry O. H.Laoh , MS and Lorraine W.Th. Sondakh , SP ., MP as member .The objective of this research is to determine the welfare level of potato farmers basedon marketing channels of potatoes in Makaaruyen Village Modoinding Sub District.This research was conducted in Makaaruyen Village Modoinding Sub District , occurred inMarch of 2014. Data collected in this study are primary and secondary data . Primary datawere obtained from 40 respondents potato farmers , and secondary data obtained from theinstitutions associated with this study that is BP3K District of Modoinding , ModoindingDistrict Office , and BKKBN Manado. Data collecting used simple random sampling method.The research result showed that there were 2 marketing channel that can be comparedstatistically namely :1. Channel 1 : Farmer collecting trader consumer2. Channel 2 : Farmer collecting trader retailer consumerT test result indicated that at marketing channel 1 is larger than the farmer welfare level atmarketing channel 2.